An explorative study on I.T. and systems librarianship focusing on competencies, tasks, and responsibilities in the library setting - Cerdeno, Chris Gianni C. (2014)
Since libraries are increasingly becoming more and more dependent on information systems and technologies in terms of their collection and services, a closer analysis on the position which caters to these aspects of library life have to be developed to incorporate IT and systems librarianship and pave the way for its establishment. In line with this, this study focused on the perceptions various experts and practitioners in the field regarding the profession.